Integrating New Technologies into Curriculum - Kazhenova, M.M.; Zhussupova, R.F. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
This article examines the impact of innovative methods in foreign languagevteaching. Their constant use allows making mindset of the students open to innovations, teaching them to be proactive and creative, since these qualities are the features of innovative teaching. Technology integration is the use of technology resources – computers, mobile devices like smartphones and tablets, digital cameras, social media platforms and networks, software applications, the Internet in daily classroom practices, and in the management of a school or university. The integration of technology should serve to guide, expand and enhance learning objectives. It is understood that teachers and students do need to spend time learning the basics of using a computer. This is necessary in order to move to effectively integrating technology. Curriculum integration with the use of technology involves the infusion of technology as a tool to enhance the learning in a content area or multidisciplinary setting. Technology enables students to learn in ways not previously possible. Effective integration of technology is achieved when students are able to select technology tools to help them obtain information in a timely manner, analyze and synthesize information and present it in a professional way